Library developement project as a modern youth center - Minchenko E. Y., Rassokhina I. Y. (Pedagogics and psychology: relevant theoretical and practical questions, 2016)
The results of sociological investigations (questionnaring) on the theme “Students and libraries” are presented. The investigation was made among the students in October 2016 within of the project of development of library as a modern youth center.
Keywords: проект; студенты; эффективность; библиотека; students; efficiency; project; library